1988
DOI: 10.1210/jcem-66-1-33
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Stimulate Cortisol Production by Cultured Human Adrenocortical Cells

Abstract: Studies using cultured human adrenocortical cells were performed to determine if the immune modulation of glucocorticoid production previously described in animal studies also occurs in humans. Human monocytes significantly increased (P less than 0.001) cortisol production from adrenocortical cells after 24, 48, and 72 h of culture. This stimulation was not CRH dependent, and the presence of CRH alone did not augment cortisol production. The active factor was soluble, since supernatants of monocyte cultures st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 17 publications
0
24
2
Order By: Relevance
“…Lastly, we did not observe type I IL-l mRNA in mouse adrenal glands, a finding at odds with some reports describing a direct effect of IL-l on adrenal cortical cells (Roh et al, 1987;Whitcomb et al, 1988;Andreis et al, 1991). However, two recent studies have failed to find any acute stimulatory effect of IL-1 on glucocorticoid secretion at the level of the adrenal gland (Naito et al, 1990;Harlin and Parker, 199 1).…”
Section: Discussioncontrasting
confidence: 99%
“…Lastly, we did not observe type I IL-l mRNA in mouse adrenal glands, a finding at odds with some reports describing a direct effect of IL-l on adrenal cortical cells (Roh et al, 1987;Whitcomb et al, 1988;Andreis et al, 1991). However, two recent studies have failed to find any acute stimulatory effect of IL-1 on glucocorticoid secretion at the level of the adrenal gland (Naito et al, 1990;Harlin and Parker, 199 1).…”
Section: Discussioncontrasting
confidence: 99%
“…One pathogenic mechanism might relate to perturbations in the homeostatic interplay between the HPA axis and the immune system, in the form of cytokines (Jenkins and Grossman, 1997). It has been clearly established that interleukins (ILs) 1α, IL-1ÎČ, IL-6 and IL-2 are all able to exert a direct stimulatory effect on adrenocortical cortisol secretion (Roh et al, 1987;Whitcomb et al, 1988;Salas et al, 1990;Tominaga et al, 1991;O'Connell et al, 1994), with the stimulatory effects of IL-1α and IL-1ÎČ being suggested to be mediated via prostaglandins (PGD 2 , PGF 2 and PGE 2 ) (Winter et al, 1990;Tominaga et al, 1991). Furthermore, IL-6 has been shown to act synergistically with physiological concentrations of ACTH in stimulating cortisol secretion (Salas et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the inflammatory cytokines TNF␣, IL-1, and IL-6 all seem to play a role in local immune-adrenal regulation. IL-1 induced corticosteroid biosynthesis in vivo independently from ACTH and caused glucocorticoid secretion in hypophysectomized rats (55), perfused rat adrenals (56), and dispersed human adrenal cells (57). IL-6 stimulated corticosterone release from rat adrenocortical cells alone and in synergy with ACTH, an effect probably mediated and amplified by PGs (58).…”
Section: Immune-adrenal Interactionsmentioning
confidence: 99%